Behind the image : research in photography - Fox, Anna.; Caruana, Natasha (Lausanne, Switzerland : AVA Academia, 2012)
'Research Methods' is a lively exploration of how to undertake research. It brings together a wide range of different approaches and invites learners to consider innovative approaches to the way they work.
boek